Development and Standardization of Indigenized Emotional Intelligence Scale - Shruti Marwaha , (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
The coetaneous study was effectuated to develop and validate a self-report measure of Emotional Intelligence. With an aim to develop a reliable and valid measurement instrument of emotional intelligence based on mixed model, the mixed model of emotional intelligence and literature on it were investigated, and then an item pool with 60 items was developed. Fourteen experts of emotional intelligence examined 72 items. In order to make the expert’s judgments standardized, Law she Content Validity Ratio was used. As a result of the ratio analysis, 12 items were discarded from initial draft of the scale. Data were collected from a sample of 1664 individuals including 874 men and 790 women recruited from different cities of India for the exploratory factor analysis whose results indicated the scale includes unidimensionality. Results indicated that the scale is reliable and valid instrument in measuring emotional intelligence. Construct validity was supplemented by finding its relationship with peer rating and correlation was found to be moderately positive. The Scale is a reliable and valid measure with good items homogeneity, internal consistency and a meaningful pattern.